Increasing self-protection skills of children staying in women's shelters with body safety training: a child sexual abuse prevention study - Çıtak-tunç, Gülseren; Eser, Dilek; Kılınç, Fatma (The European Research Journal, 2023)
Objectives: Child sexual abuse is a risk for children living in a happy family environment, as well as for children under state protection who have problems in achieving family unity. Methods: The study was conducted with 17 children between 3-7 years of age staying at women’s shelters with their mothers and aimed to improve their sexual abuse recognition and self-protection skills. 7 children identified as experimental group were provided with the Body Safety Training program and the effect of the training was evaluated with the “What If” Situation Test. The test results in the experimental group were compared with 10 children in the control group and the test was repeated three weeks later in order to determine the persistance of the training. Results: The data obtained were evaluated by non-parametric analysis and Kruskal Wallis, Wilcoxon-signed Rank Test were used in addition to Mann Whitney U tests to determine the difference between the groups. As a result of the research, “What If” Situation Test sub-dimension mean scores showed an increase in favor of the post-test in the experimental group, but no significant increase was observed in the control group. Conclusions: This difference observed in the experimental group shows that the Body Safety Training program is an effective program to increase self-protection skills for preventing sexual abuse in children.